Hypoxia due to patent foramen ovale in the absence of pulmonary hypertension. - Maraj, R (1999)
In most patients with a patent foramen ovale, blood flows from the left atrium to the right atrium in the absence of pulmonary hypertension. Our report describes a patient with a patent foramen ovale in whom flow occurred from the right atrium to the left atrium in the absence of pulmonary hypertension. We discuss hemodynamic findings and present a brief review of the pertinent medical literature regarding this phenomenon. We also discuss the role of transesophageal echocardiography in the diagnosis of this condition and in the elucidation of the underlying mechanisms, and we suggest several mechanisms that may explain the occurrence of this phenomenon in our patient.